Strengthening Character Education Developing Key Personality Traits Individuality Holistic Education Perspective : Penguatan Pendidikan Karakter Mengembangkan Kepribadian Utama Entitas Individualiteit Perspektif Pendidikan Holistik - Wahyuni, Akhtim; Yusuf, Arbaiyah (Indonesian Journal of Education Methods Development, 2026)
General Background: Holistic education emphasizes the formation of whole human beings through balanced development of spiritual, intellectual, emotional, social, aesthetic, and physical potentials. Specific Background: In the Indonesian educational context, strengthening character education has become a national priority to cultivate ethical, responsible, and value-oriented students. Knowledge Gap: Despite the growing emphasis on character education, limited empirical descriptions exist regarding how holistic education frameworks are implemented in schools to develop the core personality of students, particularly within the concept of individualiteit. Aims: This study aims to describe the main personality of the individualiteit entity developed at SMA Muhammadiyah 2 Surabaya and to examine the strategies used to strengthen character education from a holistic education perspective. Results: Using a qualitative approach with interviews, observations, and documentation, the study found that the main personality developed in the school focuses on Islamic character grounded in students’ faith (aqidah) and manifested through integrated development of spirituality, intellectuality, emotional maturity, aesthetics, and physical well-being. The strengthening strategy is implemented through three interconnected approaches: class-based character education, school culture–based programs, and community participation initiatives involving parents, alumni, and professionals. Novelty: The study presents an integrated model of holistic character education centered on Islamic values and the development of the individualiteit entity within a school environment. Implications: These findings demonstrate how holistic educational practices can systematically integrate classroom learning, institutional culture, and community engagement to cultivate comprehensive student personality development. Highlights: Islamic value orientation grounded in aqidah forms the core framework of student personality formation. Integrated programs connect spirituality, intellectual growth, emotional maturity, aesthetics, and physical development. Educational practices combine classroom activities, institutional traditions, and community engagement mechanisms. Keywords: Character Education, Main Personality, Individuality, Holistic Education